PENGEMBANGAN KOMPETENSI DIGITAL LEADERSHIP BAGI SEKOLAH MENENGAH KEJURUAN - Maman Suryaman; Lila Setiyani; Tiawan, Tiawan; Dedih, Dedih; Sudiono, Sudiono (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2023)
Digitalization has been adopted by the education sector. Successful adoption requires leadership that understands IT strategy. SMKN in Karawang is a vocational-based educational institution that tries to implement link and match with industry and has tried to encourage successful technology adoption. The concept of digital leadership has become part of the framework that can guide organizations to be successful in adopting and utilizing technology, so that they can achieve their vision optimally. This community service activity aims to develop digital leadership competencies for school structures. This service procedure is carried out by evaluating the ability to adopt technology in schools, which is then explained regarding digital leadership development strategies. This activity was attended by 23 SMKN schools in Karawang Regency with a total of 46 participants. The results of this service were able to provide inspiration for school structures to digitize all existing processes in schools. Apart from that, the understanding absorbed by the participants can be used as material in preparing a school development strategy plan